(untitled) (مجلة البحوث الأكاديمية, 2017)
1,3-Bis (4-hydroxybenzylidene)acetone I was used as starting material for preparing new unsaturated polyesters. These polyesters were synthesized by utilizing interfacial polycondensation technique of 1,3-bis (4-hydroxy benzylidene) acetone I with adipoyl, sebacoyl, isophethaloyl, terephethaloyl and 4,4’-diphenic dichloride. In order to characterize these polymers, the necessary model compound II was prepared by reacting I and benzoyl chloride. The structure of I, II and produced polyesters were confirmed by elemental and spectral analysis. Additionally, solubility, reduced viscosity of the polyesters in the range of (0.52 - 0.76 dl/g) were determined. The thermal properties of the polymers were evaluated by thermogravimetric analysis and correlated with their structural units. The crystallinitiy of some polyesters were tested.